2022
DOI: 10.3390/jpm12081244
|View full text |Cite
|
Sign up to set email alerts
|

The Octopus Trap of Takotsubo and Stroke: Genetics, Biomarkers and Clinical Management

Abstract: Takotsubo cardiomyopathy (TC) is a reversible cardiomyopathy mimicking an acute coronary syndrome, usually observed in response to acute stress situations. The association between acute ischemic stroke and TC is already known, since it has been previously reported that ischemic stroke can be both a consequence and a potential cause of TC. However, the precise pathophysiological mechanism linking the two conditions is still poorly understood. The aim of our review is to expand insights regarding the genetic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…About 90% of TCM cases are found in women, specifically postmenopausal women, with a mean age of 67-70 years and the risk is about 10 times higher in women than men [ 18 - 19 ]. Several studies have shown that TCM is associated with a history of depression, anxiety, and type-D personality because of an increased norepinephrine response to emotional stress and the presence of identifiable stressful triggers in two-thirds of cases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 90% of TCM cases are found in women, specifically postmenopausal women, with a mean age of 67-70 years and the risk is about 10 times higher in women than men [ 18 - 19 ]. Several studies have shown that TCM is associated with a history of depression, anxiety, and type-D personality because of an increased norepinephrine response to emotional stress and the presence of identifiable stressful triggers in two-thirds of cases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Takotsubo cardiomyopathy which is first described in 1990 is derived from the Japanese term “octopus trap” [ 1 ]. This form of cardiomyopathy is more common in the elderly population with a post-menopausal female preponderance [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…They commonly present with chest pain, dyspnea, and syncope and less commonly, signs of heart failure, tachy/bradyarrhythmias, cardiogenic shock, mitral regurgitation, and sudden cardiac arrest [ 7 ]. Transient ischemic attacks or strokes are likely to develop due to embolization from apical thrombus [ 1 ]. ECG abnormalities show ST-segment elevation, depression, QT prolongation, T inversion, and nonspecific changes as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation